HUBUNGAN ANTARA KEBIASAAN MAHASISWA PEMINUM ALKOHOL DENGAN DISKRIMINASI PADA PEMABUK DAN SOCIAL DRINKER DI DENPASAR - Widiadnyani, Luh Gede Erika; Zuryani, Nazrina; Ranteallo, Ikma Citra (JURNAL ILMIAH SOSIOLOGI: SOROT; Vol 3 No 1 (2023): JISSOROT, 2023)
This research is motivated by the existence of dangerous habits in students such as smoking, consuming alcoholic beverages and the worst is the use of illegal drugs (drugs). This study aims to find out how significant the relationship between student drinking habits and discrimination against drunkards and social drinkers in Denpasar using the scalpel of Ted Robert Gurr's theory of discrimination. This study used a proportionate stratified random sampling technique for 91 respondents, namely FISIP Unud students who live in Denpasar City. In order to prove and analyze this, determining the correlation coefficient (R), multiple linear regression test as well as the F-test and T-test. The results of the t-count test at show drunk discrimination is 2.243 and social drinker discrimination 3.342. The F-count results obtained were 22.062, it means there is a significant positive relationship between the habit of drinking student alcohol and discrimination against drunkards and social drinkers in Denpasar. The strength of the relationship formed (R) is 0.578. The resulting coefficient of determination is 33.4% which is the percentage contribution of variables X to Y. Meanwhile, the other 66.6% is explained by another factors. Based on the results of this study, it is highly recommended that the coefficients on the drunkard and social drinker variables do not develop exponentially and should decrease with increasing age into maturity of students . Keywords: Teenagers, Alcoholic Beverages, Discrimination